2017
DOI: 10.3934/biophy.2017.3.337
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and applications of the anti-inflammatory effects of photobiomodulation

Abstract: Photobiomodulation (PBM) also known as low-level level laser therapy is the use of red and near-infrared light to stimulate healing, relieve pain, and reduce inflammation. The primary chromophores have been identified as cytochrome c oxidase in mitochondria, and calcium ion channels (possibly mediated by light absorption by opsins). Secondary effects of photon absorption include increases in ATP, a brief burst of reactive oxygen species, an increase in nitric oxide, and modulation of calcium levels. Tertiary e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
459
3
46

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 716 publications
(585 citation statements)
references
References 103 publications
11
459
3
46
Order By: Relevance
“…In the present study, PBM at 780 nm (70 mW and 8 J) led to an increase in TGF‐ β mRNA after 2 and 4 days. This difference could be related to the different amounts of energy delivered in the 2 studies 10, 111, 3, 25…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, PBM at 780 nm (70 mW and 8 J) led to an increase in TGF‐ β mRNA after 2 and 4 days. This difference could be related to the different amounts of energy delivered in the 2 studies 10, 111, 3, 25…”
Section: Discussionmentioning
confidence: 99%
“…The effects of PBM on macrophage phenotypes are beginning to be described in cell cultures studies,10, 30, 31, 32, 33, 34 evidencing that this therapeutic modality, especially using the NIR wavelength, is capable of altering the polarization of these cells in vitro. In vivo experiments have demonstrated that PBM (808 nm) can shift the phenotype of brain microglial polarization from the pro‐inflammatory phenotype (M1) to the anti‐inflammatory (M2) phenotype after ischemic stroke, promoting cortical neurogenesis 35.…”
Section: Discussionmentioning
confidence: 99%
“…Low levels of light at these wavelengths modulates the release of nitric oxide (NO) (Uozumi et al, 2010) and increases both cerebral oxygenation (Wang et al, 2017) and blood flow (Salgado et al, 2015). Besides these effects, transcranial PBM can stimulate neurogenesis (Tanaka et al, 2011) and provide neuroprotection via antioxidant, anti-neuroinflammatory, and anti-apoptotic activities (De Taboada et al, 2011; Hamblin, 2017; Lu et al, 2017; Salehpour et al, 2017; Salehpour et al, 2018a). In particular, it has been demonstrated that transcranial PBM is able to increase regional cerebral blood flow in MDD patients (Schiffer et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, cytochrome c oxidase and nitrozated proteins were considered as the major targets of light . Recently, there has been increasing evidence that cryptochromes and opsins , mediate the cell's response to visible and UV light. All this suggests that there are several molecular targets, which could intercept a photon of light and trigger multiple signaling cascades.…”
Section: Introductionmentioning
confidence: 99%